Penentuan Kandungan Phthalate Plastisizer DEHP (Bis (2-ethylhexyl) phthalate) pada Kemasan Makanan, Minuman dan Obat/Kosmetik Berbahan Plastik Dengan Metode EN71-5 Menggunakan GC-MS - Wisnu Setya Nugraha; Budhi Indrawijaya (Program Studi Teknik Kimia, Universitas Pamulang, 2023)
Food, beverage, medication, and cosmetic packaging are just a few examples of the numerous plastic items available today. Behind the shapes, colors, and size variations available on the market, the usage of plasticizers, which are additives that work to increase the resistance and flexibility of plastic materials, is one of the risks that hound consumers. The phthalates ester DEHP, which is a form of hazardous chemical called bis (2-ethylhexyl) phthalate, may be present in this plasticizer. Phthalates, according to research, can lower the level of the hormone testosterone, which in turn alters how the male reproductive system develops. From the research, phthalates have been linked to cancer also. Using the EN71-5 procedure, phthalate compounds in plastic products can be analyzed. The process of sample preparation involved extraction using a soxhlet extractor and the organic solvent n-Hexane. The samples were then subjected to GC-MS analysis. Because it offers high selectivity and accuracy in assessing complex chemical molecules, both quantitatively and qualitatively, the GC-MS (Gas Chromatography-Mass Spectrometer) is utilized. According to the analysis findings, the sample complies with Permendag No. 26 Tahun 2021's quality standards for goods containing hazardous chemicals because the amount of the phthalates DEHP (Bis (2-ethylhexyl) phthalate) compound was below the instrument's detection limit or it was not found in the sample. This sample test's findings only relate to the samples and/or products that were used in the test.